The Role of Quality in Sociotechnical Systems - Brogt, Tobias; Schiller, Barbara; Schuler, J. Peter M.; Eicker, Stefan (Proceedings of AMCIS 2017 - Twenty-third Americas Conference on Information Systems, 2017)
Today, value is co-created in sociotechnical systems in which different stakeholders integrate resources (products and services) in an interactive process. For these systems to be successful, quality is very important. However, existing systems often fail to deliver the right level of quality, and the available quality approaches seem to be insufficient. Therefore, this paper provides insight into the role of quality by applying a service system perspective. We show that a holistic quality perception that reflects the modern expectations of stakeholders is necessary. In addition, different resources for modern services and their interaction need to be taken into account. This results in the need for quality management specific for sociotechnical systems, which integrates different existing approaches to cover these demands. Furthermore, the authors suggest future research on perceived quality and technical support in this context.
Keywords: Quality; sociotechnical system; service system; value co-creation; stakeholder